2013
DOI: 10.1136/vr.f7381
|View full text |Cite
|
Sign up to set email alerts
|

Suspected adverse events, 2012

Abstract: Increase in serious adverse events; Increase in reports involving products marketed under the Small Animal Exemption Scheme; Decrease in injection site reactions. These are some of the results from the surveillance work carried out by the pharmacovigilance unit at the Veterinary Medicines Directorate (VMD), as discussed by Giles Davis and colleagues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
2
2
0
Order By: Relevance
“…This distribution of adverse events by animal species is similar to that obtained by Naidoo and Sykes [26] in South Africa, Coulibaly [22] in Ivory Coast, Assoumy et al [10] in Senegal and Davis et al [27] in Britain who showed that dogs were the main species affected by ADRs after administration of veterinary drugs at proportions of 60, 51, 39 and 41%, respectively. Also, intense clinical activities are oriented towards canine medicine in these countries resulting in a high incidence of adverse drug effects in these species.…”
Section: Discussionsupporting
confidence: 86%
“…This distribution of adverse events by animal species is similar to that obtained by Naidoo and Sykes [26] in South Africa, Coulibaly [22] in Ivory Coast, Assoumy et al [10] in Senegal and Davis et al [27] in Britain who showed that dogs were the main species affected by ADRs after administration of veterinary drugs at proportions of 60, 51, 39 and 41%, respectively. Also, intense clinical activities are oriented towards canine medicine in these countries resulting in a high incidence of adverse drug effects in these species.…”
Section: Discussionsupporting
confidence: 86%
“…However, these findings also indicate that no vaccines were risk-free and that other factors also can be associated with the development of FISS [ 59 ]. The latter finding is also supported by the data from the UK VMD receiving notifications of FISSs in cats vaccinated with MLV, inactivated, and recombinant vaccines [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Feline Injection-site Sarcoma (Fiss)supporting
confidence: 56%
“…Many causes of inflammation could be associated with FISS development, and FISSs can occur in animals following vaccination with inactivated, recombinant, modified live vaccines as well as with non-vaccine injections, e.g., in the UK, the VMD received notifications of FISSs in cats associated with different vaccines. However, these reports did not take the number of injected vaccines into account [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In a prospective case-control study conducted at the University of California, Davis, USA, it was demonstrated that, among injections, vaccines were more frequently associated with FISS development compared to other compounds; amongst vaccines, the risk was significantly higher when adjuvanted vaccines were used [ 59 ].…”
Section: Feline Injection-site Sarcoma (Fiss)mentioning
confidence: 99%
See 1 more Smart Citation